1998
DOI: 10.1111/j.1365-2621.1998.tb17918.x
|View full text |Cite
|
Sign up to set email alerts
|

High Hydrostatic Pressure Effects on Vegetable Structure

Abstract: Cryo-fracture scanning electron microscopy revealed the changes that cauliflower and spinach leaves undergo after treatment with high hydrostatic pressure. High pressure changed cell permeability and enabled movement of water and metabolites from inside to outside of the cell. The ultrastructure showed that parenchyma organization disappeared in spinach leaf and cavity formation occurred after treatment. However, cauliflower exhibited a firm structure with a soaked appearance and would be more suitable than sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 10 publications
7
60
0
1
Order By: Relevance
“…This is in good agreement of previous report that the changes in firmness of fruits and vegetables were exhibited in 2 stages, including the loss in firmness followed by the upturn phase (24). The rapid drop in textural properties and the steady recovery may result from the high pressure effects on biological systems, which include constant pulse and continuous hold actions of pressure (24)(25)(26). The released enzymes such as pectinmethylesterase catalyze methylation and then involve the gel-like network formation with divalent ions, which is responsible for an increase in hardness of vegetables (4,24).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is in good agreement of previous report that the changes in firmness of fruits and vegetables were exhibited in 2 stages, including the loss in firmness followed by the upturn phase (24). The rapid drop in textural properties and the steady recovery may result from the high pressure effects on biological systems, which include constant pulse and continuous hold actions of pressure (24)(25)(26). The released enzymes such as pectinmethylesterase catalyze methylation and then involve the gel-like network formation with divalent ions, which is responsible for an increase in hardness of vegetables (4,24).…”
Section: Resultssupporting
confidence: 92%
“…1D, 1H) of carrot and spinach samples also depended on the pressure level and process time. The integrity of carrot and spinach leaves was disrupted by high pressure, leading to molecular reorganization of outer-layer components (26,27). The textural attributes were relatively less affected at 100 MPa.…”
Section: Resultsmentioning
confidence: 98%
“…However, Butz and coworkers [7] observed that the macroscopic appearance of onion slices was unaffected by HPP at 300 MPa for 30 min, indicating that cell wall destruction had not occurred in this case. At an even higher pressure of 400 MPa for a hold time of 30 min, SEM micrographs showed that cauliflower and spinach cells had collapsed and intercellular fluid had replaced the intercellular air spaces [9].…”
Section: Introductionmentioning
confidence: 99%
“…Textural changes in plant tissues caused by pressure treatments may occur as a result of physical disruption of the tissue. A group of researchers observed cellular structure changes and membrane folding of cauliflower and spinach leaves after HP processing at 400 MPa with cryofracture scanning electron microscopy (Prestamo and Arroyo 1998). Microscopic studies of onion epidermis cells revealed severe damage to the vacuoles after 300 MPa treatments at 25°C (Butz et al 1994).…”
Section: Texturementioning
confidence: 99%